Effects of chocolate intake on Perceived Stress; a Controlled Clinical Study - Al Sunni, Ahmed (Int J Health Sci (Qassim), 2014)
BACKGROUND: Cocoa polyphenols have been shown to reduce stress in highly stressed, as well as normal healthy individuals, we wondered whether commercially available chocolate could reduce perceived stress in medical students or not, so we decided to conduct this study. METHODS: Sixty students were divided into 3 groups (10 males + 10 females/group): i) Dark chocolate (DC) ii) Milk chocolate (MC) iii) White chocolate (WC). Subjects answered a PSS-10 (Perceived Stress Scale) questionnaire at baseline and after consumption of chocolate (40 g/day) for 2 weeks. Data were analyzed by using Microsoft Excel and SPSS version 20. Descriptive analyses were conducted. Means were compared across the study groups by One-Way ANOVA and within the same group by paired ‘t’ test. RESULTS: Mean stress scores compared between the groups by ANOVA revealed statistically not significant differences before (F =0.505; P=0.606) and after chocolate consumption (F=0.188; P=0.829). Paired ‘t’ test compared stress scores means before and after chocolate supplementation within the same group and exhibited statistically significant decrease in DC (t = 2.341; p value = 0.03) and MC (t = 3.302; p value = 0.004) groups. Mean stress scores decreased, on average, by approximately 2 and 3 points in DC and MC groups, respectively, at 95% Confidence Interval. The difference was more evident and statistically significant in female students as compared to the males. CONCLUSION: Consumption of 40 g of Dark and Milk chocolate daily during a period of 2 weeks appear to be an effective way to reduce perceived stress in females.